SOURCES NITROGEN IN BEAN WINTER IN SUCCESSION TO GRASS WITH AND WITHOUT inoculation Azospirillum brasilense:ECONOMIC ANALYSI - Sabundjian, M. T.; Arf, O.; Kaneko, F. H.; Nascimento, V. (Revista Brasileira de Engenharia de Biossistemas, 2014)
In production systems, nitrogen is absorbed and one of the most important nutrients for the beans, on the other hand, the nutrient is applied in larger amounts and thus the more onerous than the cost of production of the legume. With this, the present study aimed to evaluate the economic viability of doses of nitrogen on grain yield of winter bean crop grown under no-tillage after different cultures. The experiment was installed in the experimental area belonging to the Faculty of Engineering - UNESP, Single Island, in Selvíria (MS), with an altitude of 335 meters. The soil type is clayey Oxisoil (EMBRAPA, 2006). The experimental design was a randomized block design with 16 treatment arranged in a 4x4 factorial design with four replications. The treatments consisted of four cover crops (corn and / or Urochloa ruziziensis or not inoculated with Azospirillum brasilense) and doses of nitrogen (0, 40, 80 and 120 kg ha-1). The plots were made over an area of 7 lines (spaced 0.45 m) corn with 5 m long. The economic analysis was performed according to the technique of partial budgeting, detailed in Noronha (1987). It is recommended to obtain a larger increase in grain yield and higher profit margin Bean winter sprinkler irrigated no-till application of 80 kg ha-1 of nitrogen in beans in succession to sole maize to inoculation Azospirillum brasilense.